Financial Rumors in the Context of Monetary Crimes - Hamza, Hassan; Abdallah, Faras (Journal of Legal Sciences, 2026)
Rumor is a strange mixture of reality and imagination. It is difficult to identify the realistic elements and separate them from the fictional aspects, or they are devoid of any truth. Financial rumors play a major role in the reality of Iraqi society. Indeed, the Iraqi citizen is more vulnerable to what is rumored than what is announced, broadcast, or what people transmit among themselves. This is the reality of Iraqi society. Financial rumors aim to create a state of monetary instability and the spread of anxiety, fear, and hesitation, trying to create a state of Ambiguity over the decisions and instructions regarding the regulation of currency and the movement of capital within the country undermines confidence in the national currency with the aim of weakening it and creating an unreal impression of the strength of foreign exchange, which creates a state of instability in its price and speculation within the markets, which disrupts the internal economic situation, which reflects negatively on the reality of monetary policy. In particular and economic policy in general. The purpose of this research is to study the impact of misleading financial rumors on currency and the extent to which these rumors contribute to bringing about changes in the structure of economic society and the formation of monetary crimes. Financial rumors are many and their sabotage goal is dangerous because they relate to the daily and necessary needs of citizens in general and those dealing in the financial and monetary market in particular.